(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper aims to investigate the work and thought of William Kentridge through the different meanings revealed by the concept and practice of performance. The interaction of different artistic fields and experiences, both in art and life, is implied in Kentridge’s work and poetics; this analysis reveals that his position as an artist never disregards ethic and political responsibility. Performative dimension operates not only in the multiplicity of genres and techniques, but also in the complex of relationships arising around the different works of the South-African artist. The essay investigates, as a representative example, the series of works developed around The Magic Flute, particularly the metaphors and themes contained in the Black Box project (2005), considered “in the light” of shadow.